2021
DOI: 10.4274/tjo.galenos.2020.07377
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Sequential Bilateral Vitrectomy Surgery for Retinopathy of Prematurity: A Single Surgeon Experience

Abstract: Objectives: We report the safety and efficacy of simultaneous bilateral vitrectomy for stage 4 and stage 5 retinopathy of prematurity (ROP). Materials and Methods: Babies who had immediate sequential bilateral vitrectomy surgery for stage 4 or stage 5 ROP were included in this retrospective study. Clinical history, demographic characteristics of the patients, surgical procedure details, perioperative and postoperative ophthalmic and systemic complications, and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 28 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Ten studies (one prospective and nine retrospectives) involving 782 patients (1179 eyes) were eligible. [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] The quality of all studies was good according to the NIH quality assessment tool [Table 1]. These studies were conducted in different parts of the world: five were conducted in India, [ 1 , 16 , 17 , 20 , 21 ] three in Turkey, [ 13 , 14 , 18 ] one in Italy, [ 15 ] and one in the United States of America (USA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies (one prospective and nine retrospectives) involving 782 patients (1179 eyes) were eligible. [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] The quality of all studies was good according to the NIH quality assessment tool [Table 1]. These studies were conducted in different parts of the world: five were conducted in India, [ 1 , 16 , 17 , 20 , 21 ] three in Turkey, [ 13 , 14 , 18 ] one in Italy, [ 15 ] and one in the United States of America (USA).…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] The quality of all studies was good according to the NIH quality assessment tool [Table 1]. These studies were conducted in different parts of the world: five were conducted in India, [ 1 , 16 , 17 , 20 , 21 ] three in Turkey, [ 13 , 14 , 18 ] one in Italy, [ 15 ] and one in the United States of America (USA). [ 19 ] Most of the studies were case series; thus, the level of evidence in these studies was 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Another study done by Özdek et al, in Turkey, studied 70 eyes of babies with ROP whom underwent consecutive PPV, and reported success rates of 95.7% for stage 4a, 83.3% for stage 4b, and 50% for stage 5 (from a total of six eyes). 14 Another Turkish study done by Karacorlu et al reported a success rate of 89% for stage 4a, 63% for stage 4b, and 42% for stage 5. 15 Shah et al, in India, studied 20 eyes with ROP that underwent LSV, and reported a success rate of 100% for stage 4a and 89% for stage 4b.…”
Section: Discussionmentioning
confidence: 96%
“…18 Özdek et al reported postoperative complications in the form of cataract (2.8%), iatrogenic retinal break (1.4%), vitreous hemorrhage (11.4%), glaucoma (10%), esotropia (34%), nystagmus (20%), and phthisis bulbi (4.3%). 14 One of the factors that might govern the postoperative complication rate is premedication with intravitreal anti VEGF, supporting that was a study done by Xu et al (2013) comparing between outcomes of PPV with and without intravitreal anti-VEGF premedication, and they reported that only the PPV group exhibited a significantly higher occurrence of preretinal hemorrhage (40%) when compared to the bevacizumab+PPV group, and some complication occurred only in the former group, including; Other complications in the control group included reproliferating of the fibrovascular tissues (two eyes), cataract (two eye), vitreous hemorrhage (two eyes), and glaucoma (one eye), and two eyes received lens surgery because of dense cataracts (13%). 19 The causes of the re-detachment may be attributed to proliferative vitreoretinopathy, reopening of a previously treated break, or developing a new break (spontaneous or iatrogenic during vitrectomy), 20 timing might help in identifying the cause, earlier re-detachments are more likely to be duo to new/re-opening of breaks, while late ones are attributed to peripheral vitreal traction.…”
mentioning
confidence: 99%